Leaders stumble : an elder considers his case book - Loader, David; Centre for Strategic Education (Vic.) (East Melbourne, VIC : Centre for Strategic Education, 2020)
"In the era of COVID-19, the author states, families, schools, businesses and nations are looking for leadership. As an 'elder', he advises educational leaders to look within themselves and learn to live with the uncertainty and ambiguity of a chaotic, fast-changing world. He notes that stumbling forward is how leaders already operate in real-life settings, that they need to be honest about the problems faced, offer credible hope that a solution can be found, enlist the community's support in creating a solution and act courageously and empathetically, knowing that all decisions will be imperfect when the future is unknowable and the present only partially understood." -- Back cover.
Includes bibliographical references (page 14)
Keywords: Educational leadership; Educational leadership